(untitled) (Ozone Therapy Global Journal, 2016)
DM is a chronic metabolic disorder due to an absolute or relative defect in the production and / or release of effective insulin that leads to an alteration in the metabolism of carbohydrates, proteins and lipids, which results in an increase in Blood and urine glucose concentrations, and blood lipid concentrations Complications of the lower limbs are one of the leading causes of hospitalization in diabetic patients. Lower limb ulcers (mainly caused by diabetic neuropathy) occur in approximately 15% of patients, and amputation has an incidence of close to 1%. Peripheral neuropathy leads to protective sensorial loss of pain and autonomic dysfunction (with sympathetic denervation, dry skin and local temperature rise) Knowing the therapeutic properties of ozone and its multiple applications we consider it as the first choice therapy for the treatment of diabetic foot ulcers.